Schools, Justice, and Immigrant Students: Assimilation, Race, Ethnicity, Gender, and Perceptions of Fairness and Order. Issue 7 (July 2015) - Peguero, Anthony A.; Bondy, Jennifer M.
Background/Context: Students' perceptions of justice, fairness, and order within their schools are arguably key building blocks of socialization to participation within a democratic society. The ideals of justice, fairness, and order within their schools are particularly imperative because the educational system is founded on a belief of democracy and meritocracy. It is also known that students' perceptions of school justice can vary by race, ethnicity, and gender. What remains uncertain is how the fastest growing segment of the United States, students in immigrant families, perceive the school justice, fairness, and order within their school. Purpose: The aim of this study is to explore if straight-line assimilation, segmented assimilation, and immigrant optimism hypotheses explain the relationships between schools, justice, and immigration, as well as the potential role of gender, race, and ethnicity in immigrant youth perceptions of justice, fairness, and order. Participants/Subjects: This study utilizes the Education Longitudinal Study of 2002 (ELS), a nationally representative sample of high school sophomores. Research Design: This study's research design includes statistical analysis of secondary data. Findings/Results: Findings do suggest that the students' perceptions of justice, fairness, and order are indeed moderated by immigrant generation, race, ethnicity, and gender. Conclusions/Recommendations: Educators and educational researchers who are seeking to better understand the schooling experiences of immigrant youth might benefit from questioning assimilation and Americanization as processes that inevitably promote educational progress. Given that immigrant youth are and have historically been marginalized within U.S. schools, it appears that socialization, Americanization, gender, and immigrant generational status are germane to creating democratic education for all students. Attentiveness to democratic school justice, order, and fairness is, therefore, imperative.